Operation and function of the tricarboxylic acid cycle in the illuminated leaf - Nunes-Nesi, A; Sweetlove, L; Fernie, A (2007)
Respiratory activity of plants in the light, measured as carbon dioxide release from the tricarboxylic acid (TCA) cycle or oxygen consumption by the respiratory chain, is generally reported to lie between 25 and 100% of that in the dark. While this has been interpreted as evidence for an inhibition of respiration during photosynthesis, an increasing body of evidence indicates that mitochondrial respiration plays an important role in photosynthetic tissues. Historically, the view from experiments using specific respiratory inhibitors has been that oxidative phosphorylation in the mitochondria provides the cytosol with adenosine triphosphate even in the light. However, functioning of TCA cycle reactions is also required for the export of carbon skeletons necessary for nitrate reduction in the cytosol. In addition, export of TCA cycle-derived reducing equivalents may also be necessary for photorespiration (for hydroxypyruvate reduction in the peroxisomes). The work with respiratory inhibitors has recently been complemented by a range of transgenic experiments that provide direct evidence for the importance of the TCA cycle in the illuminated leaves. These transgenesis experiments hint at an important role for ascorbate in coordinating the major pathways of energy metabolism within the leaf and are in keeping with current thinking that redox signals emanating from the mitochondria are important in setting the cellular machinery to maintain overall redox balance. In this review we intend to synthesize recent experimental data to postulate a model of the function of the TCA cycle in the illuminated leaf. © Physiologia Plantarum 2007.